2007
DOI: 10.1590/s1517-97022007000200013
|View full text |Cite
|
Sign up to set email alerts
|

Nem toda pessoa cega lê em Braille nem toda pessoa surda se comunica em língua de sinais

Abstract: ResumoO trabalho foi definido tendo como objetivo discutir e explicitar algumas das diferenças existentes, quanto ao acesso à informação e à comunicação, entre aquelas pessoas que, embora possuam deficiências semelhantes, vivenciam discapacidades diferentes. O recorte metodológico aplicado foca especificamente as pessoas com deficiência visual e as com deficiência auditiva, não simultâ-neas, com ênfase às pessoas com surdez e às com cegueira. O arcabouço conceitual utilizado é o mesmo que o adotado pela classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
18

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
0
8
0
18
Order By: Relevance
“…By segmenting these results according to the health field, the use of the ICF has the following division into Brazilian research: neurology, observed in 16 publications 11,16,18,21,23,34,35,38,39,[46][47][48][49][50][51]54 ; orthopaedics, in 12 publications 15,19,22,24,25,27,28,30,32,41,42,45 ; health surveillance, in two 36,43 ; HIV, in two 29,55 ; women's health 40 , endocrinology 31 , hearing and visual deficiencies 10 , gerontology 37 and public health 52 , in one publication each.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By segmenting these results according to the health field, the use of the ICF has the following division into Brazilian research: neurology, observed in 16 publications 11,16,18,21,23,34,35,38,39,[46][47][48][49][50][51]54 ; orthopaedics, in 12 publications 15,19,22,24,25,27,28,30,32,41,42,45 ; health surveillance, in two 36,43 ; HIV, in two 29,55 ; women's health 40 , endocrinology 31 , hearing and visual deficiencies 10 , gerontology 37 and public health 52 , in one publication each.…”
Section: Resultsmentioning
confidence: 99%
“…There are another 25 institutions that appear with one publication each [10][11][12][15][16][17][18]21,23,24,26,[35][36][37][38][39][40]42,43 . It is important to note that there are articles that were published by more than one educational institution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample consisted of 20 students with the following profiles: 12 female and 8 male; 8 high school graduate and 12 college graduate; and 15 oralized and 5 non-oralized. According to Torres [Torres et al 2007], oralized deaf are those who have developed more skills in a oral-auditory language, compared to those non-oralized, whose verbal skills are quantitatively and qualitatively inferior.…”
Section: The Reading Modulementioning
confidence: 99%
“…Segundo Monteiro (2010, p. No entanto, é preciso alertar que as pessoas com cegueira e baixa visão enfrentam dificuldades referentes ao acesso à informação e à comunicação, pela falta de recursos financeiros para adquiri-los e falta de escolas e professores capacitados (TORRES; MAZZOZI; MELLO, 2007;MIRANDA, 2002).…”
Section: Segundo Beck (2007)unclassified